DETERMINATION OF RESPONSIBILITIES, WORK FACILITIES AND WORK DISCIPLINE WITH WORK MOTIVATION AS A MEDIATOR VARIABLE ON EMPLOYEE PERFORMANCE TAX MANAGEMENT AGENCY AND RETREBUTION FOR THE CITY OF BATAM - Reny Nozariyanti; Indrayani Indrayani; Muammar Khaddafi; Ayu Rahmasari; Rajesh Rila (RADJA PUBLIKA, 2022)
In this study, researchers used data respondents, such as gender, age and long working respondents to provide information on the characteristics of respondents. The questionnaire was spread over 48. The discussion in this chapter is the result of field studies to obtain data on the questionnaire responses that measure five key variables in the study, namely responsibility, work facilities, work discipline, work motivation and employee performance. Analysis of data with parametric and non parametrics statistics using SEM-PLS (structural Equation Modelling-Partial Least Square) on the research variables, instrument test, normality test, hypothesis test, as well as discussion of the hypothesis test results and path analysis Path. This research uses path analysis to test relationship patterns that reveal the influence of variables or a set of variables against other variables, both direct influences and indirect influences. Calculation of line coefficient in this study assisted with Smart PLS Ver 3.0. To find out the direct and indirect influences between variables then be seen from the calculation result of the line coefficient and to know the significance. The influence of the variable X3 on X4 has a P-Values value of 0,000 <0.05, so it can be stated that the influence between X3 on X4 is significant. The effect of the X3 variable on Y has a P-Values value of 0,005 <0.05, so it can be stated that the effect between X3 on Y is significant. The influence of the variable X4 on Y has a P-Values value of 0.008 <0.05, so it can be stated that the influence between X4 on Y is significant. The influence of variable X1 to X4 has a P-Values value of 0.039 <0.05, so it can be stated that the influence between X1 to X4 is significant. The effect of the variable X1 on Y has a P-Values value of 0.017 <0.05, so it can be stated that the effect between X1 on Y is significant. The influence of variable X2 on X4 has a P-Values value of 0.006 <0.05, so it can be stated that the influence of X2 on X4 is significant. The influence of the variable X2 on Y has a P-Values value of 0.008 <0.05, so it can be stated that the influence between X2 on Y is significant.